Venous resection during pancreatectomy for pancreatic cancer: a systematic review - Wang, Xiaobo; Demir, Ihsan Ekin; Schorn, Stephan; Jäger, Carsten; Scheufele, Florian; Friess, Helmut; Ceyhan, Güralp O. (Translational Gastroenterology and Hepatology, 2019)
Pancreatic cancer is one of the most aggressive and lethal malignancies with a dismal prognosis and survival. The curative effects of venous resection (VR) in pancreatic cancer remain controversial. A systematic literature search was performed in PubMed, Embase and the Cochrane Library. The overall postoperative complications, perioperative mortality, histopathology, and long-term survival were compared between patients undergoing pancreatectomy combined with (VR+ group) or without (VR− group) VR. Forty-one studies were included in the systematic review. Pancreatectomy combined with VR required longer operation time and led to increased perioperative blood loss, whereas postoperative complications were similar. Patients in the VR+ group showed larger tumors and reduced R0 rates. Regarding long-term survival, patients with VR+ seemed to have impaired 1-, 3-, and 5-year survival. Based on our results, VR in pancreatic cancer is a safe and feasible procedure. Given the fact that patients have miserable outcomes and survival in the palliative setting alone, extended resection including VR is required for the purpose of achieving radical resection.